Conjugation of Different Aflatoxin Derivatives to Proteins and Their Use as Heterologous Antigens in Immunoassay Development. Issue 17 (1st May 2019) - Ertekin, Özlem; Kocaağa, Harun; Öztürk, Selma
Abstract: Analysis of small molecule contaminants using biochemical methods like ELISA or biosensors often require their conjugation to a bigger molecule. Protein conjugates of aflatoxins (AFs), potent carcinogenic mycotoxins, are widely used in antibody and analytical assay development. There are more than 20 naturally occurring AF derivatives four of which are regulated by international authorities. AFB1, the most abundant AF derivative, is also the most commonly utilized one in protein conjugation reactions. In this study, we demonstrated that the use of different AF derivatives can is an aid for modifying the conjugation efficacy to obtain optimal hapten densities. With a Mannich‐type reaction scheme, AFG1 and AFG2 conjugates showed more than 3‐fold higher hapten densities compared with AFB1 and AFB2 conjugates. We also showed that the use of heterologous antigens in AF immunoassay development decreases the production costs without affecting assay sensitivity. Abstract : Aflatoxin‐protein conjugates that are used in AF assay development are traditionally produced with AFB1 derivative. In this work, authors used four common naturally occurring derivatives of AFs for Mannich type conjugation reaction. AFG1/G2 derivatives resulted in 3 fold higher conjugation ratio compared to AFB1/B2 derivatives and increased the signal intensity of the developed immunassay without affecting the assay sensitivity.